Invasion, Impact and Control Techniques for Invasive Ipomoea hildebrandtii on Maasai Steppe Rangelands - Ojija, Fredrick; Manyanza, Ndaki Marco (Journal of Basic & Applied Sciences, 2021)
The ecosystem integrity of the Simanjiro Maasai steppe rangeland in Tanzania is threatened by the invasive plant Ipomoea hildebrandtii Vatke. However, its invasion status, impact and control techniques are unclear in the country. We conducted a study in Terrat and Sukuro villages in Simanjro District, Tanzania, to assess its invasion status and impact across grassland–woodland habitats using point sampling techniques. Key informant interviews and questionnaires were used to assess techniques used by the Maasai pastoralists to control I. hildebrandtii. A total of 10 plots (70 m2 each) with 9 quadrats (1 m2 each) in the invaded and non–invaded sites were established to study I. hildebrandtii invasions. The impact of I. hildebrandtii on rangelands was investigated by comparing herbage (herbaceous vegetation) species composition, richness, basal cover and biomass productivity between invaded and non–invaded plots. Results revealed that I. hildebrandtii invasion was higher in grass woodland habitats (90%) than in non-invaded plots. Non–invaded plots exhibited higher biomass productivity (0.289 ± 0.03 t DM/ha) than invaded plots (0.202 ± 0.02 t DM/ha). Furthermore, non–invaded plots had a higher basal cover (grasses: 54.71 ± 1.95%, forbs: 45.29 ± 1.95%) compared with invaded plots. We also recorded high native plants abundance in quadrats with low I. Hildebrandtii density (22.00 ± 1.36). Additionally, 81% of Maasai pastoralists reported to manually (uproot) control I. hildebrandtii. Based on the results of our study, we recommend further research and novel control techniques coupled with education to be implemented in the Simanjiro.